IMPROVING THE STUDENTS’ READING COMPREHENSION THROUGH QUESTION AND ANSWER RELATIONSHIP (QAR) READING STRATEGY - Prihatin Puji Astuti (Lexeme : Journal of Linguistics and Applied Linguistics, 2019)
Abstract This research investigated the use of Question and Answer Relationship Reading Strategy in increasing the students’ reading comprehension achievement. The research aimed to find out to what extent the improvement of the students’ reading comprehension achievement after being treated using Question and Answer Relationship (QAR) reading strategy. This research was conducted at the grade XII students of SMK Sasmita Jaya 2, Tangerang Selatan. This reaseach administrated cluster random sampling in taking the sample then decided two classes as the samples, one class was treated using QAR reading strategy and the other class was not. The method of the research was quantitative research under quasy experimental research. The result of the research shows that there was significant improvement of their reading comprehension after being treated using QAR reading strategy and there was also significant difference between the the students who were treated using QAR reading strategy and the students who were not.Keywords: Comprehension, Reading, Strategy, Students, QAR